ANALISIS KORELASI SEKTOR PERTANIAN TERHADAP PERSENTASE TINGKAT KEMISKINAN DAN KETIMPANGAN KABUPATEN JEPARA - Anandar, Anatansyah Ayomi (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2022)
The role of the agricultural sector in economic development is very important because most people in Jepara Regency depend on this sector. This study aims to analyze the relationship between the agricultural sector to the percentage of poverty and inequality in Jepara Regency. The data used is data on the growth rate of the Gross Regional Domestic Product (GRDP) of Jepara Regency on the basis of constant prices by business field (percent) and the percentage of poor people in 2011-2020. The data analysis method used is Spearman Rank correlation analysis. Based on the results of the study, the correlation coefficient value is 0,733, which means that the agricultural sector variable has a significant relationship with the percentage of poverty and inequality in Jepara Regency.